Cutaneous Vasculitis and Central Nervous System Infarctions due to Varicella Zoster Virus Vasculopathy in an Immunocompromised Patient. (6th April 2020) - Flores Rosario, Karen; Michelis, Katherine C.; Bjorkman, Carol; Araj, Faris G.
Abstract : Varicella zoster virus (VZV) infection commonly presents as varicella during childhood, and zoster, later in life. Here, we present a rare and interesting case of VZV infection that manifested with both cerebral and spinal infarctions and cutaneous vasculitis in the absence of a classic vesicular rash in an immunocompromised patient.